How To Entice Employees?: an Attempt to Reduce Labor Turn Over - Andi Juanna; Agus Hakri Bokingo Hakri Bokingo (Journal of International Conference Proceedings (JICP), 2018)
Employee dissatisfaction with work is the reason why employee turnover rates are currently experiencing a significant increase. Especially in private companies, turn over is a benchmark in determining whether the organization's performance is stable or not. The fact that the discharge of employees from the company is caused by the treatment received is indisputable. Various strategies are implemented in order to generate job satisfaction. However, it is not enough to provide solutions to reduce employee turnover. Efforts to increase employee satisfaction and loyalty are antecedents to improving service, customer satisfaction, and customer loyalty (Dahl and Peltier, 2014). Strong internal marketing strategies can be important to achieve and maintain competitive advantage and encourage organizational change and improve organizational performance. By using an internal marketing scheme, it is expected that it can help management (companies) to satisfy employees, so that employees will be able to carry out their duties in carrying out services to consumers.